Efeitos da associação do hipoclorito de cálcio e ácido fosfórico na resistência de união entre dentina e resina composta - Giusti, Flávia Maria (2015)
The aim of this study was to evaluate the effect of pretreatment of dentin with calcium hypochlorite (Ca (OCl) 2) associated with the phosphoric acid on the bond strength of composite resin. For this fifty six sound human molars were selected. The coronal portion of the tooth was cut and the teeth were divided into 8 groups according to the substances concentration (phosphoric acid to 35% or 10% and Ca (OCl) 2 = 10%, 20% or 30%) and association of substances single (+) or step in two steps, as follows: A35; A35Ca10; A35 + Ca 10; A35 + CA20; A35 + CA30; A10 + Ca 10; A10 + A10 + CA20 and CA30. The prepared teeth were restored with adhesive system Ambar (FGM) and composite resin. The samples were sectioned into beams 1mm2 cross sectional area, which were submitted to microtensile test in universal testing machine at 0.5 mm / min until failure. The data (MPa) were analyzed by Kruskal-Wallis and Dunn (α = 0.05). The groups that were treated with the dentin demineralization conventional protocol (A35- 30.2 MPa) and deproteinized in two steps (A35Ca10 - 19.3 MPa) had the highest bond strength values, with similar statistically (p> 0 , 05). The other groups had lower bond strength values were statistically similar. Therefore it is concluded that the combination of phosphoric acid with calcium hypochlorite was effective in the group that used the A35Ca10 and A35 + Ca10 concentrations